Wasting and sudden cardiac death in hemodialysis patients: a post hoc analysis of 4D (Die Deutsche Diabetes Dialyse Studie) - Drechsler, Christiane; Grootendorst, Diana C.; Pilz, Stefan; Tomaschitz, Andreas; Krane, Vera; Dekker, Friedo; März, Winfried; Ritz, Eberhard; Wanner, Christoph (American journal of kidney diseases, 2011)
Background - Wasting is common in hemodialysis patients and often is accompanied by cardiovascular disease and inflammation. The cardiovascular risk profile meaningfully changes with the progression of kidney disease, and little is known about the impact of wasting on specific clinical outcomes. This study examined the effects of wasting on the various components of cardiovascular outcome and deaths caused by infection in hemodialysis patients. - Study Design - Prospective cohort study. - Setting & Participants - 1,255 hemodialysis patients from 178 centers participating in Die Deutsche Diabetes Dialyse Studie (4D) in 1998-2004. - Predictor - Moderate wasting was defined as body mass index, albumin, and creatinine values less than the median (26.7 kg/m2, 3.8 g/dL, and 6.8 mg/dL, respectively) and C-reactive protein level less than the median (5 mg/L) at baseline. Severe wasting was defined as body mass index, albumin, and creatinine levels less than the median and C-reactive protein level greater than the median at baseline. - Outcomes & Measurements - Risks of sudden cardiac death (SCD), myocardial infarction (MI), stroke, combined cardiovascular events, deaths due to infection, and all-cause mortality were determined using Cox regression analyses during a median of 4 years of follow-up. - Results - 196 patients had wasting (severe, n = 109; and moderate, n = 87). Overall, 617 patients died (160 of SCD and 128 of infectious deaths). Furthermore, 469 patients experienced a cardiovascular event, with MI and stroke occurring in 200 and 103 patients, respectively. Compared with patients without wasting (n = 1,059), patients with severe wasting had significantly increased risks of SCD (adjusted HR, 1.8; 95% CI, 1.1-3.1), all-cause mortality (adjusted HR, 1.8; 95% CI, 1.4-2.4), and deaths due to infection (adjusted HR, 2.3; 95% CI, 1.2-4.3). In contrast, MI was not affected. The increased risk of cardiovascular events (adjusted HR, 1.5; 95% CI, 1.0-2.1) was explained mainly by the effect of wasting on SCD. - Limitations - Selective patient cohort. - Conclusions - Wasting was associated strongly with SCD, but not MI, in diabetic hemodialysis patients. Nonatherosclerotic cardiac disease potentially has a major role to account for the increased cardiovascular events in patients with wasting, suggesting the need for novel treatment strategies.